The interplay of self-assessment mechanisms and socialization processes in promoting tax compliance - Wirawan, I Made Dwi Sumba; Adyatma, I Wayan Chandra; Edwindra, Riza (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2024)
Taxation plays a crucial role in Indonesia as it serves as a significant revenue source for the country. Small and Medium Enterprises (SMEs) are particularly important in the economic landscape of Indonesia. This study underscores the significance of tax compliance among Small and Medium Enterprises, particularly in light of global economic challenges and the essential need for tax revenues. Tax compliance is a critical determinant in sustaining government functions and fostering economic growth in Indonesia. It is vital for governments to fulfill their financial obligations, including the provision of public goods, national defense, and support for economic development. However, factors such as tax socialization, understanding of tax regulations, and the application of tax knowledge influence the level of compliance among Micro, Small, and Medium Enterprises (MSMEs). The objectives of this research were to examine the impact of the self-assessment system on tax compliance among MSMEs in Indonesia, and to investigate the mediating role of tax socialization in the relationship between the self-assessment system and tax compliance. This study examined micro, small, and medium-sized business taxpayers in Denpasar City, utilizing a sample size of 100 taxpayers selected through simple random sampling. The findings indicate that self-assessment systems have a positive impact on the compliance behavior of these MSME taxpayers. However, the results suggest that tax socialization does not significantly moderate the relationship between the self-assessment system and taxpayer compliance.